Investigation of the Relationship Between Blood Gas and Oxidative Stress Parameters in Calves with Diarrhea - Kızıl, Meltem; Çalışkan, Mehmet; Geçmez, Kübra; Baykal, Asya; Akça, Burak (My University, 2025)
The aim of this study was to determine the etiology of diarrhea in neonatal calves with diarrhea and to determine the changes in blood gases and oxidative stress parameters. 20 diarrheal calves and 20 healthy calves brought to Fırat University Faculty of Veterinary Medicine Animal Hospital were used in the study. After identifying the etiological agents in diarrheic calves using immunochromatographic test kits, blood samples were collected from the jugular vein for further analysis. Blood gas parameters were measured using a blood gas analyzer. Additionally, serum malondialdehyde (MDA), reduced glutathione (GSH), glutathione peroxidase (GSH-Px), catalase (CAT), and superoxide dismutase (SOD) levels, as indicators of oxidative stress, were analyzed using a spectrophotometer. Blood gas analysis revealed that pH, bicarbonate (HCO3-), and partial oxygen pressure (pO2) levels were decreased, whereas partial carbon dioxide pressure (pCO2) and serum potassium (K) levels were elevated. When compared to the serum MDA levels of healthy calves, it was determined that the serum MDA levels of calves with diarrhea increased significantly, while the serum GSH, GSH-Px, CAT and SOD enzyme activities decreased. As a result of this study, it was concluded that, independent of the etiological agents causing diarrhea, metabolic acidosis will develop in addition to oxidative stress in the neonatal period, and that serum HCO3- levels may decrease and electrolytes, especially K, may increase.
Keywords: Oxidative stress; calf; Diarrhea; blood gases